Acceptability of Novel Small-Quantity Lipid-Based Nutrient Supplements for Complementary Feeding in a Peri-Urban South African Community. (December 2015) - Rothman, Marinel; Berti, Cristiana; Smuts, Cornelius M.; Faber, Mieke; Covic, Namukolo
Background: Small-quantity lipid-based nutritional supplements (SQ-LNS) may potentially be used for home fortification in poor settings, where low nutrient-dense complementary foods are commonly used for infant feeding. However, they need to be acceptable to succeed. Objective: This study assessed the acceptability of 2 novel, SQ-LNS (A and B) for supplementing complementary foods among infants aged 6 to 12 months in a peri-urban South African community. Methods: Both supplements were soy-based pastes and contained micronutrients and essential fatty acids. In addition, supplement B contained docosahexaenoic acid, arachidonic acid, phytase andl -lysine. Mother–infant pairs were enrolled in a 2-part trial. Part 1 ( n = 16) was a test-feeding trial with a crossover randomized design, and a 5-point hedonic scale was used for sensory evaluation ( disagree = 1, agree = 5). Part 2 ( n = 38) was a 2-week, home-use trial followed by focus group discussions. Results: In part 1, more than 70% of mothers reported a score ≥4 on sensory attributes for both SQ-LNSs indicating that both supplements were well perceived. In part 2, the mean reported consumption over the 2-week period was 65.3% ± 34.2% and 62.0% ± 31.3% of the 20 g daily portion for supplements A and B, respectively. Focus group discussions confirmed a positive attitude toward the supplements in the study population. Conclusion: This study showed acceptance of both SQ-LNSs in terms of sensory characteristics as well as in terms of practicality for home use.